USM TO FOCUS ON TeRamPiL FOR ACADEMICS’ HOLISTIC DEVELOPMENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – Universiti Sains Malaysia (USM) will introduce TeRamPiL as the basis for its academics’ future career development.